Natureal® oat bran instant drink - Mikola, Markku (MTT, 2004)
Dietary fiber in diet is of high importance when trying to fight the global epidemic of overweight and obesity. To obtain viable options for enriching the diet with dietary fiber more applications are needed. The aim of this research was to study a blood glucose response lowering and dietary fiber giving serving of oat bran. A new oat bran powder was developed and an application model was constructed followed by a clinical study. High Beta glucan, heat-treated commercial oat bran: Natureal® GI-flour was developed. The aim was an oat bran of high solubility of Beta glucan and a high viscosity in physiological conditions. This was then introduced to a classical drink powder format for measuring the glycemic index. Also the effect of oat bran on glycemic response was measured. The clinical study was done with 12 type 2 diabetic subjects. This combination of the product and application gives a low postprandial glucose response. The results indicated that oat bran is capable of in an active manner to lower the response of external glucose given simultaneously. It also gives a viable option for introducing in a simple palatable form a substantial amount of daily need of dietary fiber. This product forms high viscosity in physiological conditions and at the same time introduces substantial amounts of good quality macronutrients. Oat protein is of high value, comparable to that of soy protein and the fat is mostly of unsaturated fat. Here we have shown a good option for helping the global problem of obesity in a form of natural oat bran giving very high viscosity.
Keywords: Ka; oat bran; glycemic response; viscosity; obesity